Ostracoda: database for the Neogene of Portugal - Meco, I. (2010)
The "Ostracoda: database for the Neogene of Portugal", prepared under the Project "POCTl/36531/PAL/2000 - Studies on Portuguese Palaeontology / Post-Paleozoic", is presented. It provides information about 158 especies that have been recognized in sections and boreholes concerning Neogene units in Portugal.